Credit management procedure: a study on Dhaka Bank Limited, foreign exchange branch, Dhaka - Naher, Nur-Un (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration, 2016.